The expectation-performance gaps on entry-level graduates’ vocational skills: A study in Wuhan, China - ZHANG, JING (2018)
This study is intended to understand employers’ and students’ viewpoints on various vocational skills and to examine whether there are expectation-performance gaps on students’ vocational skills by comparing employers’ rating and their evaluation of graduates on different vocational skills in Wuhan, China. The research was undertaken by a survey and interviews with students from two universities and employers from two medium-sized companies in Wuhan. The result of this study showed that different opinions were owned by the stakeholders mentioned above and expectation-performance gaps are existing. Also, stakeholders held a lopsided view of the role of higher education that sees higher education as a skills training place and ignore its other characters such as liberal education. Moreover, the reason why there are expectation- performance gaps is also being discussed. Although the present study does have some limitations, this research contributes to Chinese accounting education and can aware other researchers to do more comprehensive analysis on this topic.